BUDDHIST INNOVATION OF THE COMMUNICATION ABOUT THE BUDDHA’S KAMMA - Promjan, Aphichat (Journal of Buddhist Innovation Review, 2023)
The results of thesis showed that the doctrine of Kamma found in Theravada Buddhist scriptures can be classified into 3 types: 1) Kamma is classified by the qualities of karmic causes 2) Kamma is classified by the sense doors of deeds 3) Kamma is classified by its nature and its consequences, called "12 Kamma." Karma can be also classified by the principle of consequences: wholesome deed and unwholesome deed. The Lord Buddha had taught about Kamma and the consequences of Kamma in detail. The Buddha’s teachings consisted of cause and effect, parables and predecessors to accompany it. Buddha teaches all people without dividing the caste of the listeners. Buddha would first examine the character of the listeners who would attain enlightenment and then communicate about wholesome deed and unwholesome deed. He uses the 4 principles and the 9 principles of teaching as the tools of communication. He himself was the person who possessed 3 miracles; marvel of physicl power; marvel of mind reading and marvel of teaching. All people who listen Buddha’s teaching on Kamma have been examined by his 10 powers of perfection wisdom (Dasa-Balanana). Therefore, it is the most perfect procession of Buddhist innovative communication.